Actual treatments for out‐of‐hospital ventricular fibrillation at critical care medical centers in Osaka: a pilot descriptive study. Issue 3 (13th March 2014) - Sakai, Tomohiko; Kitamura, Tetsuhisa; Iwami, Taku; Hayashi, Yasuyuki; Rinka, Hiroshi; Ohishi, Yasuo; Mohri, Tomoyoshi; Kishimoto, Masafumi; Kawaguchi, Ryosuke; Kajino, Kentaro; Yumoto, Tetsuya; Uejima, Toshifumi; et al.
<x xml:space="preserve">Abstract</x> Aim Although advanced treatments are provided to improve outcomes after out‐of‐hospital ventricular fibrillation, including shock‐resistant ventricular fibrillation, the actual treatments in clinical settings have been insufficiently investigated. The aim of the current study is to describe the actual treatments carried out for out‐of‐hospital ventricular fibrillation patients, including shock‐resistant ventricular fibrillation patients, at critical care medical centers. Methods We registered consecutive adult patients suffering bystander‐witnessed out‐of‐hospital cardiac arrest of cardiac origin, for whom resuscitation was attempted by emergency medical service personnel, who had ventricular fibrillation as an initial rhythm, and who were transported to critical care medical centers in Osaka from March 2008 to December 2008. This study merged data on treatments after transportation, collected from 11 critical care medical centers in Osaka with the prehospital Utstein‐style database. Results During the study period, there were 260 bystander‐witnessed ventricular fibrillation arrests of cardiac origin. Of them, 252 received defibrillations before hospital arrival, 112 (44.4%) were transported to critical care medical centers, and 35 had shock‐resistant ventricular fibrillation. At the critical care medical centers, 54% (19/35), 40% (14/35), and 46% (16/35) of shock‐resistant ventricular fibrillation patients were treated with extracorporeal life support, percutaneous coronary interventions, and therapeutic hypothermia, respectively, but their treatments differed among institutions. Some patients with prolonged arrest without prehospital return of spontaneous circulation who received advanced treatments had neurologically favorable survival, whereas approximately two‐thirds of shock‐resistant ventricular fibrillation patients with advanced treatments did not. Conclusion This pilot descriptive study suggested that actual treatments for prehospital ventricular fibrillation patients differed between critical care medical centers. Further studies are warranted to evaluate the effectiveness of in‐hospital advanced treatments for ventricular fibrillation including shock‐resistant ventricular fibrillation.